The effect of super-chilled preservation on shelf life and quality of beef during storage - TIAN,Tian (2022)
Abstract The effect of super-chilled storage (-2 °C) on shelf life and quality of beef was investigated, compared with chilled (4 °C) and frozen (-18 °C) storage. The pH value, color, TVB-N, water-holding capacity, total viable counts (TVC) and sensory evaluation were used to evaluate the freshness, shelf life and quality of beef. These results indicated that the fresh beef stored in super-chilled condition demonstrated better pH and color stability compared to chilled storage, and exhibited better water-holding capacity and sensory score compared to frozen storage. Based on the TVB-N level and TVC, the super-chilled storage was conducive to prolong the shelf life of beef with good quality. The super-chilled storage is a good way to preserve freshness of fresh beef. In conclusion, this work provides data for the preservation of fresh beef which will benefit the meat industry.